Embracing Industry 4.0 - Guidelines for Managers - Sabraz Nawaz, Samsudeen (International Journal of Psychosocial Rehabilitation, 2020)
The industry 4.0, or Fourth Industrial Revolution (used interchangeably in this context), as it has been more broadly known, can potentially change the way modern organizations design, manufacture, deliver, and service their products. However, due to the lack of a universal framework for the application of Industry 4.0, businesses find it challenging to become a part of the revolution. Managers primarily encounter difficulties in planning the implementation without any proper guidelines. Hence, the article aims to find an answer to the question, “What factors managers should consider when they apply the fourth industrial revolution?”Towards that end, this research carries out a literature review to obtain primary data from academic articles on the implementation and application of Industry 4.0/the fourth industrial revolution. This study eventually came up with ten factors that should be considered by managers in the application of Industry 4.0, apart from delineating several limitations as well as issues. Implications wise, this study would facilitate practitioners and managers properly.